Mulā‘amat Ma‘āyīr al-Amrīkī līī-Ta‘līm al-Lughah al-Ajnabiyyah (ACTFL) fīī Tatwīr Manāhij al-Lughah al-‘Arabiyyah - Azizah, Aprilya; Zalila, Nur; Muhajir; Siregar, Nurlina; Nabilah, Farah Farhatun (Mantiqu Tayr: Journal of Arabic Language, 2026)
Arabic language learning in Indonesia continues to face challenges regarding standardized assessment systems that are consistent and globally measurable, as existing curriculum dominated by structural-theoretical approaches. This study aims to analyze the relevance of the American Council on the Teaching of Foreign Languages (ACTFL) proficiency standards in Arabic language curriculum development, using language assessment theory as the primary evaluative framework. The research method employed is library research, utilizing content analysis of of ACTFL documents and related curriculum literature. The findings indicate that, theoretically, ACTFL possesses strong conceptual coherence with modern assessment theories through its emphasis on construct validity, authenticity, and performance orientation. The integration of ACTFL is capable of reorienting the components of objectives, materials, and teaching methodologies from rule-mastery toward functional communicative proficiency. In conclusion, ACTFL is relevant as an international standard for enhancing the quality of the Arabic curriculum in Indonesia. However, its implementation requires contextual adaptation to the characteristics of Fusha Arabic and the strengthening of educator competencies as proficiency assessors to address practicality and reliability constraints in the field.